Ecological Studies on Calotropis procera R.Br. - Sharma, Brij Mohan (Indian Forester, 1971)
The paper describes the ecology of Calolropis procera R. Br. The plant has been observed to grow mainly in coarse sandy and alkaline soils. The amount of different cations at various depths has been mentioned.Foliar analysis reveals that the plant is poor in minerals. Root studies show that the dune plants are more branched than those growing on the sandy plains. The proportion of root to shoot is considerable.An attempt has also been made to determine the relationship between the mineral contents of its healthy leaves and quantity of available nutrients. It has been found that foliar calcium and nitrogen increase with a corresponding increase of these elements in the soli.